Occupational Health and Safety: Multijurisdictional Evaluation of Reproductive Health, Harassment, Sexual Harassment, and Violence Using SGBA+ - Jahel, Fatima (Université d'Ottawa / University of Ottawa, 2024)
Background: Occupational hazards have a high potential to adversely impact the sexual and reproductive health of workers regardless of gender or sex. In Canada, workers' reproductive health and safety are protected by federal and provincial/territorial occupational health and safety (OHS) legislation and related policies. It is unknown whether these policies include directives to protect workers from exposure to reproductive health hazards, harassment, sexual harassment, and violence in the workplace. This thesis explores whether Canadian federal and provincial/territorial OHS and related legislation address reproductive health protections for all workers and employees (women+ and men), including pregnant workers' safety, harassment, sexual harassment, and violence in the workplace. Materials and Methods: We adopted the READ approach (readying your materials, extracting data, analyzing data, and distilling findings), a systematic procedure to conduct a policy content analysis to evaluate Canadian federal and provincial/territorial OHS legislation, employment standards and human rights codes all enacted between 2013 and 2023. Data analysis included thematic content analysis to identify codes organized into themes and a frequency analysis of key concepts. We used an SGBA+ (Sex and Gender-Based Plus Analysis) to apply a gender equality lens to our exploration of Canadian legislation in the context of reproductive health protections, harassment, sexual harassment, and violence protection. Results: Our findings revealed a widespread recognition of workplace accommodations for pregnant workers, including pregnancy and parental leaves, in Canadian OHS legislation; however, there was little recognition of workplace-related adverse reproductive health outcomes for workers in federal and provincial/territorial OHS and related legislation. Although gender identity/expression and sexual orientation discrimination to protect harassment are well recognized in the federal and provincial/territorial human rights codes, our review of the Canadian federal and provincial/territorial OHS legislation and employment standards suggests a substantial gap in addressing workplace sexual harassment and violence. Conclusion: Our review of Canadian federal and provincial/territorial occupational health and safety legislation suggests a substantial gap in addressing workplace sexual/reproductive health. An all-hazards/universal precautions approach, not a focused reproductive health protection-specific approach, was adopted within OHS legislation to manage workplace risks. Harassment was mainly recognized with less robust discussion of sexual harassment and violence protections. This thesis revealed a need to modernize Canadian OHS legislation to explicitly address workplace-related reproductive health safety concerns and protections for sexual/gender-based harassment and workplace violence.
Keywords: Legislation; Sex; Gender; Women+; Men; Pregnancy; Fertility; Fetus; Stillbirth; Miscarriage; Workplace; PPE; Leaves; Gender Identity/Expression; Sexual Orientation; Discrimination; Harassment; Sexual Harassment; Gender-Based Harassment; Violence